Pengaruh Kompetensi Guru Terhadap Hasil Belajar Ekonomi Dengan Motivasi Belajar Sebagai Mediator : Survei Terhadap Siswa Kelas X SMA Negeri 2 Kuningan - Anisya Numimit; Iskandar, Iskandar; Atin Nuryatin (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
The researcher conduct this study motivated by the results of students’ achievement on Economic daily tests are mostly still below average or as known as Minimum Completeness Criteria (KKM). This research aims to find out the influence of teachers’ competence on students’ learning achievement with learning motivation as a mediator in economic subjects. The researcher use survey as the research method. To obtain the data, the researcher use the questionnaire as the main instrument in this research. The research objectives in this research are as follows: learning achievement; teacher competence; and learning motivation. Meanwhile, the research objectives are Class X students SMAN 2 Kuningan with 139 samples. For the analysis technique, the researcher use multiple regression analysis with mediation. The results of the analysis show: (1) a general description of learning achievement is in the sufficient category, teacher competency is in the moderate category, also learning motivation is in the moderate category; (2) teacher competency has a positive influence on students’ learning achievement; (3) learning motivation partially mediates the influence of teacher competence on students’ learning achievement in the economic subject